We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
104
1
avatar

(sqrt (8) - sqrt (12) ) / (sqrt (2) - sqrt (3) i Don't know how to solve it in steps

 Nov 20, 2018

Best Answer 

 #1
avatar
+1

(sqrt (8) - sqrt (12) ) / (sqrt (2) - sqrt (3)
Sqrt(8)=sqrt(4 x 2)=2sqrt(2)
Sqrt(12)=sqrt(4 x3) =2sqrt(3)
[2sqrt(2) - 2sqrt(3)] / [sqrt(2) - sqrt(3)]     factor out 2 on LHS
2[sqrt(2) - sqrt(3)] /[sqrt(2) - sqrt(3)]
All the sqrts cancel out leaving you with:
=2

 Nov 20, 2018
 #1
avatar
+1
Best Answer

(sqrt (8) - sqrt (12) ) / (sqrt (2) - sqrt (3)
Sqrt(8)=sqrt(4 x 2)=2sqrt(2)
Sqrt(12)=sqrt(4 x3) =2sqrt(3)
[2sqrt(2) - 2sqrt(3)] / [sqrt(2) - sqrt(3)]     factor out 2 on LHS
2[sqrt(2) - sqrt(3)] /[sqrt(2) - sqrt(3)]
All the sqrts cancel out leaving you with:
=2

Guest Nov 20, 2018

17 Online Users

avatar
avatar
avatar